ПОЛИМОРФИЗМ ЧЕТНЫХ ДЛИННОЦЕПОЧЕЧНЫХ Н-ПАРАФИНОВ - Платонова Н.В.; Котелъникова Е.Н.; Филатов С.К. (My University, 2006)
Polymorphous modifications of crystalline and rotary-crystalline phases, limits of solid solutions, thermal deformations, consequence and temperatures of polymorphous transformations of the even long-chain л-paraf-- fins С2бН54, C28Hsg, С30Нб2, Сз2Н6б, С34Н70 and C36H74 were determined using the X-ray powder diffraction and high temperature powder diffraction methods. Those paraffins represent the principal compounds of the natural paraffin series hydrocarbons with the general formula C„H2„+2 and they are typical representatives of rotary crystals. The study has revealed the multiplicity of low-temperature crystalline polymorphous modifications (stable, metastable and stabilized phases) of the even long-chain л-paraffins (n = 26, 28, 30, 32, 34 and 36), which wasn't observed previously for all the short-chain paraffins (n < 24) and the odd long-chain ones (n = 25 and 27). The variety of modifications depends on the lenght of molecula (« number), way of production (Fis-her-Tropsh method or crystallization from hexan), mode of thermal treating (sharp or slow cooling of the melt) and homological purity of specimen. It was revealed that the phase transition from crystalline to the low-temperature rotary-crystalline state {cryst -» rot. 1) took place for all the studied even long-chain л-paraffins (и = 26, 28, 30 and 32). Transition from the low-temperature rotary-crystalline state into the high-temperature rotary-crystalline one {rot.l - rot.2) runs only for triclinic n-paraffin (n = 26), monoclinic compounds (n = 28, 30 and 32) do not improve it due to lack of time - they start melting. The phase transitions of monoclinic n-paraffins {cryst - rot.l - L) are irreversible with temperature, and in this way they are principally differing from triclinic (n = 18, 20, 22, 24 and 26) and orthorhombic (n = 17, 19, 21, 23, 25 and 27) n-paraffins. These newly obtained and earlier experimental data allow to demonstrate that the whole range of phase transitions {cryst - rot.l - rot.2 - L) is improved only by «intermediate» {n = 22, 23, 24, 25 and 26) members of the n-paraffin homological series.